PENGARUH TAX AMNESTY DAN FAKTOR LAINNYA TERHADAP KEPATUHAN WAJIB PAJAK - MAYANG PRATIWI; AAN MARLINAH (E-Jurnal Akuntansi TSM, 2021)
This study aims to obtain empirical evidence of variables that affect taxpayer compliance in Tangerang City. By using independent variables, namely tax sanction, tax amnesty, tax awareness, tax payer attitudes, knowledge and understanding of taxes, and tax service. The objects in this study are individual taxpayers who have NPWP in Tangerang City, have participated in tax amnesty, and have received tax services by tax officials. The sample in this study was 61 respondents who were used in the study based on criteria and sampling with the convenience sampling method. The method of data analysis was carried out with reliability test, validity test, classical assumption test, f and t test , and analysis of the coefficient of determinationThe results of this study indicate that tax amnesty has an influence on taxpayer compliance and other independent variables such as tax saction, tax awareness, knowledge and understanding of taxes, tax services, and taxpayer attitudes have no effect on taxpayer compliance.